2016
DOI: 10.1128/aem.02699-15
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Mat Communities along an Oxygen Gradient in a Perennially Ice-Covered Antarctic Lake

Abstract: Lake Fryxell is a perennially ice-covered lake in the McMurdo Dry Valleys, Antarctica, with a sharp oxycline in a water column that is density stabilized by a gradient in salt concentration. Dissolved oxygen falls from 20 mg liter ؊1 to undetectable over one vertical meter from 8.9-to 9.9-m depth. We provide the first description of the benthic mat community that falls within this oxygen gradient on the sloping floor of the lake, using a combination of micro-and macroscopic morphological descriptions, pigment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
139
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(147 citation statements)
references
References 66 publications
(87 reference statements)
8
139
0
Order By: Relevance
“…Leptolyngbya is a filamentous, globally distributed genus found in tropical, 18 temperate, 19 and polar microbial mats. 4 At a finer taxonomic scale, many of the abundant OTUs were found to be closely related to Antarctic cyanobacteria (Supplementary Fig. S4), consistent with the global distribution of cold-dwelling ecotypes of cyanobacteria.…”
supporting
confidence: 72%
See 1 more Smart Citation
“…Leptolyngbya is a filamentous, globally distributed genus found in tropical, 18 temperate, 19 and polar microbial mats. 4 At a finer taxonomic scale, many of the abundant OTUs were found to be closely related to Antarctic cyanobacteria (Supplementary Fig. S4), consistent with the global distribution of cold-dwelling ecotypes of cyanobacteria.…”
supporting
confidence: 72%
“…Similar to Antarctic lake communities, 4 potentially nitrogen-fixing cyanobacteria of the order Nostocales were rare in the deep biofilms (<0.01 % of bacterial reads) but abundant in the moat communities (6.2 %; Supplementary Fig. S3), that might indicate N-limitation or greater relative phosphorus availability in the moat area.…”
mentioning
confidence: 94%
“…In addition, Pseudanabaena sp., Leptolyngbya sp. were found inhabited in cold temperature (Jungblut et al, 2016), whereas Halomicronema sp. in hypersaline mat (Fourçans et al, 2006).…”
Section: Phylogenetic Diversity Of Bacteria and Hydrogenase Genesmentioning
confidence: 98%
“…Cyanobacteria 16S rRNA gene diversity showed that the microbial mat contained Pseudanabaena sp., Leptolyngbya sp., Halomicronema sp., Stanieria cyanosphaera, Neolyngbya maris-brasilis. These species were known as members of mat bacterial communities (Fourçans et al, 2006;Jungblut et al, 2016) except Stanieria cyanosphaera, Neolyngbya maris-brasilis which from marine benthics (Caires et al, 2018;Silva & Pienaar, 2000). In addition, Pseudanabaena sp., Leptolyngbya sp.…”
Section: Phylogenetic Diversity Of Bacteria and Hydrogenase Genesmentioning
confidence: 99%
“…ally ice-covered Antarctic lake have shown the specific assemblage of a photosynthetic microbial ecosystem(Jungblut et al, 2016;Sumner, Hawes, Mackey, Jungblut, & Doran, 2015), with cyanobac-teria forming tuft-related structures exclusively found in the oxic zone where irradiance is at its highest, whereas flat bacterial mats of anoxygenic photoautotrophs are restricted to the deeper euxinic zone experiencing lower irradiance. Thus, "elephant-skin" and tufted structures may possibly have a link with oxygenic photoautotrophic micro-organisms.…”
mentioning
confidence: 99%